Japan : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Japan. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Japan's economy is growing above potential, narrowing the negative output gap. The expansion is now broader and more balanced than in 2015, with private consumption growth turning positive and private investment strengthening on the back of residential investment. However, labor shortages are evident, wage growth remains weak, and inflation is stubbornly low. Growth momentum will carry through 2017 but would weaken in 2018 if fiscal support fades as currently scheduled. The fiscal stimulus package supports 2017 growth through higher consumption and investment. Monetary policy is expected to remain accommodative and facilitate a virtuous cycle between credit and economic growth.